Biomechanical Analysis of Shooting in Basketball: Relating Research with Training Practice - Kouvelioti Βασιλική; Stavropoulos Νικόλαος; Kellis Ελευθέριος (Inquiries in Physical Education and Sport, 2006)
The purpose of this study is to investigate shot’s and jump shot’s basic characteristics, in basketball, as they appear in qualitative and quantitative (biomechanical) studies. The angle, height and velocity of ball release, the angle of ball insertion into the hoop, the balance and the center of mass of the body, are the main biomechanical characteristics of shooting. The optimal angle of ball release varies from 35ο up to 48° and depends on the height, distance and velocity of ball release. The angle of insertion is a combination of various factors, mainly ball spin, ball trajectory, velocity, and the range of the hoop. A shot is successful when the ball falls into the basket at a range of angle relative to basket. As shot distance increases, the height of ball release decreases and the angle of ball release remains the same. Guards and forwards seem to have a greater extension and flexion range for the basic joints, than the centres. There are also differences in the shooting technique, between males and females. Further investigation on motor control and muscle activity patterns during basketball shooting is required. The alteration of shooting technique in game and fatigued conditions is not investigated.